CRIMINAL LIABILITY OF PT. AGTIKA DWISEJAHTER DUE TO THE LACK OF PERMIT RESULTING IN ENVIRONMENTAL DAMAGE IN THE PASEBAN-JEMBER AREA - Helen Pramita; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
The purpose of this study is to analyze the criminal liability that must be borne by PT. Agtika Dwisejahter as a result of conducting mining activities without the appropriate permit, which has led to environmental damage. This research also examines the impacts on the environmental and economic sectors arising from the unauthorized mining activities carried out by PT. Agtika Dwisejahter. The normative legal research method is used to analyze various legal regulations related to criminal liability in this case, including environmental protection laws and mining laws. Additionally, this research utilizes literature studies to gather relevant information and data regarding the environmental and economic impacts of illegal mining activities. The research findings indicate that PT. Agtika Dwisejahter is criminally responsible for conducting mining activities without the necessary permit, resulting in environmental damage. The study identifies various criminal sanctions that can be imposed on the company, including fines, revocation of permits, or criminal prosecution against individuals responsible within the company. Furthermore, the research reveals the negative impacts caused by PT. Agtika Dwisejahter's illegal mining activities on the environmental and economic sectors. These impacts include ecosystem destruction, land degradation, and the loss of livelihoods for local communities. Such consequences have a detrimental effect on the environmental and economic sectors, leading to a decline in the quality of natural resources and a decrease in economic development potential in the affected area. This research contributes to understanding the importance of criminal accountability for illegal mining actors in efforts to protect the environment and prevent negative impacts on the environmental and economic sectors. The resulting recommendations include stricter law enforcement against illegal mining violations, strengthening monitoring and enforcement of mining permits, as well as active participation from the community in environmental protection and monitoring of mining company activities.